SISTEM INFORMASI PERENCANAAN PEMBELIAN STOK BARANG DI TOKO LINA - Kiki Meidinasari; Nurul Kamilah; Dewi Primasari (Jurnal Ilmiah Teknologi Infomasi Terapan, 2025)
Lina Store is a business that operates in trading activities which always plans the purchase of goods for product availability in the store. In planning the purchase of goods in the shop, it is still done only with estimates, so it is difficult to determine the purchase of goods for inventory in the shop. To overcome this problem, researchers built an information system using the moving average method to calculate planning for purchasing goods to meet customer demand. The information system built is an information system for planning stock purchases at the Lina store using the PHP programming language with the CodeIgniter framework, MySQL database and run using an offline server, namely XAMPP. The results of this research are that this research has succeeded in designing and building a web-based information system for planning purchases of goods at Lina stores to overcome problems and improve the planning process for purchasing goods at Lina stores and applying the moving average method with a calculation period of 3 months. This system will be able to help Lina's shop determine the number of purchases of each item in the following month. Keywords : Moving Average, Purchases, Inventory, Information System